Cognitive Behavior Modification untuk Menurunkan Prokrastinasi Akademik Siswa Sekolah Menengah Atas - Febriani, Roiyan One; Ramli, M.; Hidayah, Nur (Jurnal Kajian Bimbingan dan Konseling, 2020)
Procrastination is a problem that many students experience. This study aimed to investigate the effectiveness of cognitive behavior modification to reduce academic procrastination of high school students. To achieve this goal, this study used a single subject design. Three male students and two female students were selected as research participants using a purposive sampling technique. Data on the rate of procrastination in the baseline 1 (A1), intervention (B) and baseline 2 (A2) phases were obtained from the academic procrastination observation sheet. The data were then analyzed using visual graphic analysis with the split middle method. The analysis showed a decrease in academic procrastination behavior in each student after cognitive behavior modification intervention. This proves that the cognitive behavior modification approach is effective in reducing academic procrastination of high school students.